Re:Research. - Muratovski, Gjoko; Vogel, Craig M. (Intellect Books, 2019)
This collection showcases diverse perspectives in design and design research, with topics ranging from the introduction of design in the primary education sector to designing information for artificial intelligence systems. Divided into seven thematic volumes, the Re:Research series maps out where the field of design research is now.